1967
DOI: 10.1126/science.155.3767.1266
|View full text |Cite
|
Sign up to set email alerts
|

Gametophytes of Four Tropical Fern Genera Reproducing Independently of Their Sporophytes in the Southern Appalachians

Abstract: Vegetative reproduction and dispersal by way of gemmae are known to occur in four types of fern gametophytes. Although they belong to basically tropical rain-forest genera, all four types have now been discovered growing natu rally in the vicinity of Highlands, North Carolina, as clones on shady, damp rocks. Their sporophytes were rare or absent. The gametophytes are now identified as Grammitis nimbata (Jenm.) Proctor, Grammitidaceae; Hymenophyllum tunbridg ense (L.) J.Sm., Hymenophyllaceae; Vittaria lineata (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 7 publications
0
56
1
1
Order By: Relevance
“…Among the taxa examined in our study, the strongest evidence for ancient asexuality is in Vittaria appalachiana, where patterns of geographical distribution and genetic diversity indicate an age of at least 10 million years (Farrar 1967(Farrar , 1978(Farrar , 1990. A study of allozyme diversity in Vittaria showed V. appalachiana to have no recent origin from or close relation to sexual Vittaria species (Farrar 1985(Farrar , 1990.…”
Section: Possible Explanations For the Pattern Of Conserved Te Sequenmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the taxa examined in our study, the strongest evidence for ancient asexuality is in Vittaria appalachiana, where patterns of geographical distribution and genetic diversity indicate an age of at least 10 million years (Farrar 1967(Farrar , 1978(Farrar , 1990. A study of allozyme diversity in Vittaria showed V. appalachiana to have no recent origin from or close relation to sexual Vittaria species (Farrar 1985(Farrar , 1990.…”
Section: Possible Explanations For the Pattern Of Conserved Te Sequenmentioning
confidence: 99%
“…In temperate regions of North America (from Alabama to New York), populations of V. appalachiana exist as independent gametophytes (i.e., with no sporophyte generation) and persist via the production of vegetative propagules termed ''gemmae.'' These populations are thought to be conspecific or closely related to the tropical species V. lineata (shoestring fern), which exists as both sporophyte and gametophyte, and reproduces sexually (Farrar 1967).…”
Section: Plant Taxamentioning
confidence: 99%
“…Gemma-producing species sometimes exist as populations that are dominated by gametophytes rather than sporophytes (e.g. Dassler & Farrar 1997) and have on multiple occasions given rise to gametophyte-only populations that reproduce clonally (Farrar 1967(Farrar , 1990.…”
Section: Pteridophytesmentioning
confidence: 99%
“…Most ferns, by contrast, propagate as perennial sporophytes and possess gametophytes that lack means of asexual reproduction. Gametophytic production of gemmae, however, has evolved in three families of predominantly epiphytic ferns [106]. Some of these ferns exist as self-perpetuating populations of gametophytes with rare, short-lived sporophytes.…”
Section: (B) Asexual Comparisonsmentioning
confidence: 99%